Leveraging Agritourism in Rural Areas in Developing Countries: The Case of Iran - Lak, Azadeh; Khairabadi, Omid (Frontiers in Sustainable Cities, 2022)
Over the past decades, agritourism has spread rapidly worldwide with the growing interest of tourists in learning about rural life and the farmers’ need to increase their income with various economic activities. Diversifying business activities on the farm, primarily through agritourism, increases the farm’s income and helps reduce the financial problems. Yet, the economic importance and consequently the cultural and social consequences of agritourism in rural areas have not been well studied, particularly in developing countries. This study explores agritourism’s cultural and economic consequences in unspoiled rural regions of Iran that have not yet experienced tourism as a sustainable economic activity. This study adopts a qualitative approach using the grounded theory method to the Varkaneh region located on the northern side of Mount Alvand in Hamedan province, Iran. Accordingly, interviews were conducted with four groups of tourists, local residents, experts, and local authorities. The interviews were transcribed and coded (open, axial, selective) using MAXQDA Software and studied through content analysis. The findings indicate that economic consequences arising from agritourism include improvement of economic development, increasing financial challenges, monetary recognition of new economic patterns, and requirement of economic, administrative measures. Cultural consequences include the emergence of cultural challenges, cultural promotion tools, culture-instilling strategies, pre-implementation management measures, post-implementation management measures, and cultural capacity development. The results could help local authorities to develop sustainable tourism plans in the rural areas with traditional agricultural livelihoods in developing countries.